Sustainability assessment of PFAS adsorbents for groundwater remediation. (2022) - Moeini, Mohammadreza; Modaresahmadi, Kiana; Tran, Tony; Reddy, Krishna R.
Abstract: Per-polyfluorinated substances (PFAS) are man-made, environmentally persistent organic chemicals with a long half-life and high solubility in water. The exacerbated concentration of PFAS in water resources causes bioaccumulation and toxicity in drinking water. Although PFAS remediation techniques have been frequently studied, assessing these methods' environmental, social, and economic impacts has rarely been considered. This study presents a sustainability assessment of two commonly used adsorbents, ion exchange resin (IX resin) and granular activated carbon (GAC), in removing long-chained PFAS from contaminated groundwater. The triple bottom line framework is used to quantify the environmental, economic, and social impacts for both IX resin and GAC. Environmental impacts are assessed with a life cycle assessment (LCA) using SimaPro. Economic sustainability is evaluated by considering direct and indirect costs and social costs of carbon using the work breakdown structure (WBS) model. Social impacts are assessed using a designed questionnaire targeting stakeholders and a social sustainability evaluation matrix (SSEM). Integrated Value Model for Sustainability Assessment (MIVES model) integrates results obtained from environmental, economic, and social sustainability assessment. The MIVES results indicated that the remediation using the IX resin unit is more sustainable compared to that using GAC.